Adaptive Base Isolation System with Elastomeric Bearings: Multi‐Stage Fiber‐Reinforced Elastomeric Bearings (MS‐FRBs) for Tailoring Response to Ground Motion Demands - Galano, Simone; Calabrese, Andrea; Konstantinidis, Dimitrios; Vassiliou, Michalis F. (Earthquake engineering & structural dynamics, 2025)
Rubber‐based devices have been widely employed in base isolation systems to safeguard essential facilities, demonstrating exceptional effectiveness under extreme lateral demands. Elastomeric isolators are designed to achieve a high vertical‐to‐horizontal stiffness ratio while maintaining stability at significant lateral displacements. However, isolating lightweight structures with these devices poses challenges, as they require relatively high vertical pressures to sufficiently shift the fundamental vibration period while ensuring stability under large deformations. Moreover, rubber degradation over time necessitates periodic, labor‐intensive maintenance, leading to elevated long‐term costs associated with bearing replacements when aging impairs performance. This paper introduces a novel elastomeric base isolation concept: the Multi‐Stage Fiber‐Reinforced Bearing (MS‐FRB) system. In this innovative approach, multiple Fiber‐Reinforced Bearings (FRBs) operate in series under shear loads, enabling substantial deformation capacity through the sequential engagement of slender rubber‐based isolators. This configuration allows precise tuning of the isolation layer's vertical and horizontal stiffnesses to accommodate varying seismic hazard levels, effectively adapting the response of rubber‐based bearings to multiple earthquake intensities. A comprehensive parametric three‐dimensional finite element analysis is conducted on bearings with diverse geometric and mechanical parameters, evaluating MS‐FRB performance under different vertical pressures, bearing shapes, and both uni‐ and bi‐directional shear loading. The system's efficacy is further assessed under realistic earthquake conditions via full 3D finite element models of two case‐study structures: low‐rise, lightweight reinforced concrete frames with and without masonry infill. Results are compared to fixed‐base configurations and those isolated with stable unbonded FRBs, highlighting the MS‐FRB's superior ability to protect structures that are typically challenging for conventional rubber‐based isolation. This work advances the application of rubber‐based devices for seismic protection, particularly in lightweight or heavyweight essential facilities, and provides a proof‐of‐concept for the design and behavior of MS‐FRBs under combined axial and shear loads.